Sikap nasionalisme dalam merebut kembali kemerdekaan Indonesia - Salafudin, Afif (Maliki Interdisciplinary Journal, 2024)
This journal examines the attitude of nationalism which is the main driving force in the struggle to regain Indonesian independence. This study aims to understand the role and importance of nationalism in mobilizing the masses and fighting the invaders during the period of the struggle for independence. This research approach uses historical analysis and literature studies such as historical documents. The results showed that nationalism played a significant role in the struggle to regain Indonesian independence. This attitude fosters the national spirit, awakens shared awareness and strengthens solidarity among the Indonesian people. This journal provides a deeper understanding of the importance of nationalism as the foundation of the struggle for independence. Through a better understanding of the national struggle, it is hoped that it can inspire present and future generations to maintain and strengthen the spirit of nationalism in building a better nation.